Process and sustainability analyses of the integrated biomass pyrolysis, gasification, and methanol synthesis process for methanol production. (15th February 2020) - Im-orb, Karittha; Arpornwichanop, Amornchai
Abstract: Technical and sustainability analyses of the methanol production via the integrated biomass pyrolysis, gasification, and methanol synthesis (IBPGM) process using rice straw as feedstock, are performed. The utilization of emitted CO2 by recycling to a gasifier as a gasifying agent is investigated for technical and environmental reasons. The effects of CO2 recirculation on the product distribution and energy consumption of the IBPGM process are examined. The production rate of methanol is improved with the increased CO2 recycle fraction, while that of bio-oil does not change. The IBPGM is a highly exothermic process, with the largest energy-releasing unit being the methanol reactor. The energy consumption at the gasifier exhibits the same trend and thermal self-sufficiency is consequently achieved when the recycle fraction is raised to 0.76. Environmental assessment using a life cycle analysis tool reveals that the energy management of methanol synthesis unit and syngas processor needs to be improved as they highly contribute toward the carbon footprint and potential environmental impact. The technical and environmental factors of the IBPGM process are evaluated by the analysis hierarchy process, calculated by a multi-criteria decision analysis method. The IBPGM process with the CO2 recycle fraction of 0.2 offers the best performance. Under this condition, the methanol and bio-oil production rates of 0.23 and 0.09 kmol h −1, respectively, and the energy efficiency of 60.7% can be achieved, based on the biomass feed rate of 1 kmol h −1 . Highlights: The methanol production from the IBPGM process is performed. Two configurations, once-through and with CO2 recirculation concepts, are compared. Suitable adjustment of CO2 recycle fraction can maximize methanol yield. Methanol synthesis reveals the highest carbon footprint. CO2 recirculation influences on the PEI of the IBPGM process.